El pensament lingüístico-literari de Teodor Llorente - Salvador, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
The literary-linguistic thought of the father of the Renaixença in Valencia (his conception of the sociolinguistic functions of Catalan, his vision of the unity of the language, his assessment of the various literary genre, etc.) forms a coherent system and can be explained by class interests which brought the Renaixença and its modernizing perspectives to a halt in Valencia.